PENGARUH PENGATURAN KERJA YANG FLEKSIBEL TERHADAP WORK-LIFE BALANCE (WLB) DAN KINERJA PEKERJA WANITA DI MASA PANDEMI COVID-19 - Anabella Nadia Nathaniel; Suharnomo Suharnomo (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze how flexible working arrangements influence work-life balance and employee performance of female workers during the Covid-19 pandemic. It also analyses the mediating effect of work-life balance between flexible working arrangements and employee performance. The research was conducted by combining quantitative and qualitative methods using an explanatory sequential mixed methods approach. Data collection in the first stage began with quantitative research through the distribution of online questionnaires, then it was continued with qualitative research through in-depth interviews. This study involved 120 female workers as respondents to the questionnaire and 3 female workers as interview participants. The data obtained implemented SEM as an analysis technique through AMOS 24.0 analysis tool for quantitative research. Findings show that flexible work arrangements have a positive and significant impact on the work-life balance and also employee performance of female workers during the Covid-19 pandemic. Other findings confirm that work-life balance take part as a mediating role in the relationship between flexible working arrangements and employee performance of female workers. Keywords: flexible working arrangements, performance, work-life balance